Evolution of Sulforaphane Content in Sulforaphane-Enriched Broccoli During Tray Drying - Reyes-Salinas, A; Saavedra-Fenoglio, A; Mahn-Osses, A (Elsevier Ltd, 2016)
Sulforaphane is a natural anticancer compound found in broccoli that comes from hydrolysis of glucoraphanin. Conversion of glucoraphanin to sulforaphane has been optimized, however, its use as functional ingredient is limited because sulforaphane is thermo-labile. We investigated the effect of drying air temperature (60, 70, 80 °C) in tray drying of sulforaphane-enriched broccoli on the evolution of sulforaphane content. Broccoli temperature and sulforaphane content were registered in time. Sulforaphane content profiles were adjusted to a first-order kinetic model, showing acceptable agreement (r > 0.90). Sulforaphane formation occurred below 40 °C; formation and degradation occurred at broccoli temperature above 40 °C, until the low content of glucoraphanin and moisture, prevents reaction. After that, only sulforaphane degradation was detected. The highest sulforaphane content at X/X0 = 0.1 was 67.6 mg/100 g DW, obtained with drying air temperature of 70 °C, being 4-fold higher than that found in fresh broccoli, and the highest reported so far in any dehydrated food. © 2016 Elsevier Ltd. All rights reserved.